1998
DOI: 10.1046/j.1365-2648.1998.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation for the relief of chronic pain: a systematic review

Abstract: The effectiveness of relaxation techniques in the management of chronic pain was determined in this systematic review of published randomized controlled trials. Reports were sought by searching MEDLINE, psycLIT, CINAHL, EMBASE and the Oxford Pain Relief Database. Studies were included in this review if they were randomized controlled trials of relaxation techniques in chronic pain. Studies which investigated the effects of relaxation in combination with other interventions were not considered. Nine studies inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 24 publications
4
41
0
Order By: Relevance
“…Although a 1996 NIH consensus panel stated that there was "strong" evidence that relaxation techniques were effective in the treatment of chronic pain, 68 a systematic review of nine randomized trials 39 found positive treatment effects in only three studies and concluded that there is insufficient evidence for the use of relaxation alone in the treatment of chronic pain. A systematic review of randomized controlled trials examining relaxation for acute pain management 60 similarly concluded that though there was "some weak evidence" to support the use of these therapies, the data were inconclusive, in part owing to methodological limitations.…”
Section: Pain Managementmentioning
confidence: 99%
“…Although a 1996 NIH consensus panel stated that there was "strong" evidence that relaxation techniques were effective in the treatment of chronic pain, 68 a systematic review of nine randomized trials 39 found positive treatment effects in only three studies and concluded that there is insufficient evidence for the use of relaxation alone in the treatment of chronic pain. A systematic review of randomized controlled trials examining relaxation for acute pain management 60 similarly concluded that though there was "some weak evidence" to support the use of these therapies, the data were inconclusive, in part owing to methodological limitations.…”
Section: Pain Managementmentioning
confidence: 99%
“…Constant symptoms are usually severe in intensity, and are associated with sleep disturbances and hence patients are likely to be in a stressful state [142]. Relaxation techniques such as deep breathing exercises, Jacobson progressive relaxation, Mitchell's relaxation method, music therapy were shown to be beneficial for chronic pain [143].…”
Section: Discussionmentioning
confidence: 99%
“…According to the 1996 National Institutes of Health report on the treatment of chronic pain and insomnia, there is strong evidence for the effectiveness of relaxation techniques in reducing chronic pain in a variety of medical conditions. Effects may include reduced pain and muscle tension, reduced anxiety and insomnia, and increased activity level (Good, 1996;Carroll, 1998). Biofeedback is one of the other psychological treatments that have been designated as an efficacious treatment for pain associated with headache and temporomandibular disorders (TMD) (Yucha, 2008).…”
Section: Psychological Treatment For Pain Among Cancer Patients By Ramentioning
confidence: 99%